Evaluasi Penjadwalan Waktu Pada Proyek Pembangunan Rumah dengan Metode CPM (Studi Kasus: Pembangunan Rumah Tinggal di Perumnas Kabupaten Karawang) - Sigit, Radyta Alicia Pramestia; Al-Muqaffa, Figar Wafiq; Sutrisno, Sutrisno (Go-Integratif : Jurnal Teknik Sistem dan Industri, 2023)
Project scheduling can help to show the relationship between the activities carried out by the project. This scheduling also functions to prioritize the travel process of a previous activity before the next activity is carried out. One scheduling method that can be used is CPM (Critical Path Method). This research aims to evaluate house construction projects in Perumnas Karawang Regency. In this research, the data taken is primary data and secondary data. Primary data was obtained directly from interviews between homeowners and researchers. The results of this research discussion showed that the critical path results were A-B-C-D-G-H-I-J-K with details of activities: preparing materials, installing foundations, assembling and installing metal slup, installing hebel, plastering walls, plastering walls, painting walls, installing ceilings and installing ceramics. Scheduling house construction projects in Perumnas Karawang Regency using the CPM method can be completed within 60 days.